Shear wave elastography: can we discover elevated diastolic filling pressures?. (8th February 2021) - Werner, AE; Bezy, S; Orlowska, M; Kubiak, G; Duchenne, J; Desmet, W; Delcroix, M; Van Cleemput, J; Ince, H; D"hooge, J; Voigt, JU
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): University Hospitals (Uz) Leuven Background:  The assessment of the left ventricular diastolic function is complex, as there is no single invasive parameter that provides a direct measurement of myocardial relaxation, myocardial compliance, or – as a surrogate - LV filling pressure. Estimation of diastolic function is therefore based on the combination of several parameters. Shear wave (SW) elastography is a novel method based on high frame rate echocardiography. SWs occur after mechanical excitation of the myocardium, e.g. after mitral valve closure (MVC), and their propagation velocity is directly related to myocardial stiffness (MS). Purpose: The aim of this study was to investigate if velocities of natural shear waves are related to MS at end-diastole (ED) and, thus, could be used to estimate left ventricular end-diastolic pressures (LVEDP) as marker of diastolic function. Methods: So far, we have prospectively enrolled 42 patients with a wide range of diastolic function, scheduled for heart catheterization so that LV filling pressures could be invasively measured. Patients with severe aortic stenosis, mitral stenosis of any degree and a more than moderate mitral regurgitation, as well as regional myocardial abnormalities or dysfunction in the anteroseptal wall were excluded. Echocardiography was performed immediately after catheterization. SW elastography in parasternal long axis views of the left ventricle (LV) was performed using an experimental scanner (HD-PULSE) at 1100 ± 250 frames per second. Tissue acceleration maps were extracted from an anatomical M-mode line along the midline of the LV septum. The SW propagation velocity at MVC was measured as the slope on the M-mode acceleration map (Figure A). Standard echocardiographic parameters of diastolic function were obtained with a high end ultrasound machine. Results: SW velocities at ED correlated well with the invasively measured LVEDP (r = 0.74, p < 0.001, Figure B). In comparison, classical echocardiographic parameters correlated only weakly with LVEDP (E/A: r = 0.398, p = 0.02, Figure C; E/E': r = 0.204, p = 0.247, Figure D). For the detection of an elevated LVEDP above 15 mmHg, a cut off value for the SW velocity at MVC of 4.395 m/s (Figure A) was associated with a sensitivity of 91.3% and a specificity of 90.9%. Conclusions: End-diastolic shear wave velocities, measured by high frame rate shear wave elastography, showed a significant correlation with the end-diastolic filling pressure of the LV and allowed to differentiate normal from elevated filling pressure which indicates a potential clinical value of the new method for a non-invasive and direct assessment of LV diastolic function. More patients will be included to confirm these findings.